2021
DOI: 10.18488/journal.aefr.2021.118.658.671
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Indirect Impact of Real Exchange Rate on Economic Growth through Foreign Trade: An Asymmetric ARDL Panel Model

Abstract: This paper aims to examine the combined effect of trade openness and real exchange rate on economic growth. We use an asymmetric ARDL panel model on a sample of Middle Eastern and North African (MENA) countries with data from 1990 to 2018. The results of the linear model prove, for the long-run component, that all variables, except government consumption, are significant. In addition, the interaction term between trade openness and the real exchange rate is negative and has a significant impact on economic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…The remarkable point of empirical results of this research are more or less similar to the study by and Qamruzzaman and Wei (2019) employing GMM which tried to figure a positive and negative shock in financial inclusion on stock market development and Pang et al, (2022) that found to be inverted U-shaped effect of urbanization on shadow economy in terms of symmetric and asymmetric short-run and long-run analysis. These results also are somehow similar to the studies by Barguellil (2021) and Mujtaba & Jena (2021) and (Mujtaba, et al, 2022) using the NARDL model which attempted to investigate the impact of Carbon dioxide emissions on economic growth and the energy consumption and population on the environmental quality. However, the uniqueness of this study is to test the harmonization results obtained by ARDL and GMM both symmetrically and asymmetrically growth analysis in the short-run and long-run.…”
Section: Empirical Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The remarkable point of empirical results of this research are more or less similar to the study by and Qamruzzaman and Wei (2019) employing GMM which tried to figure a positive and negative shock in financial inclusion on stock market development and Pang et al, (2022) that found to be inverted U-shaped effect of urbanization on shadow economy in terms of symmetric and asymmetric short-run and long-run analysis. These results also are somehow similar to the studies by Barguellil (2021) and Mujtaba & Jena (2021) and (Mujtaba, et al, 2022) using the NARDL model which attempted to investigate the impact of Carbon dioxide emissions on economic growth and the energy consumption and population on the environmental quality. However, the uniqueness of this study is to test the harmonization results obtained by ARDL and GMM both symmetrically and asymmetrically growth analysis in the short-run and long-run.…”
Section: Empirical Results and Discussionsupporting
confidence: 87%
“…The study in Barguellil (2021) used an asymmetric ARDL panel model with the data over the period of 1990 to 2018 for the Middle East and North African countries. The findings showed that the nonlinear model pointed out that there was a positive and significant asymmetric effect of the interaction variable for both upward and downward movements on the economic growth in the long run.…”
Section: The Related Literature Reviewsmentioning
confidence: 99%